PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI, PENGENDALIAN AKUNTANSI, DAN SISTEM PELAPORAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI (Studi Pada Organisasi Perangkat Daerah Kota Pekanbaru) - Asisca Weni; Rasuli M; Hasan Alamsyah Mudrika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This Study was aimed to examine the effect of the use of information technology, accounting controls, and reporting systems on the performance accountability of government agencies with organizational commitment as a moderating variable. This study used primary data by distributing questionnaires. The method of analysis used in this study is multiple linear regression analysis and moderation regression analysis. The results of this study indicate that: (1) the use of information technology has no effect on the performance accountability of government agencies, (2) accounting controls affect the accountability of the performance of government agencies, (3) the reporting system has no effect on the accountability of the performance of government agencies, (4) organizational commitment can moderate the relationship between the use of information technology on the performance accountability of government agencies, (5) organizational commitment can moderate the relationship between accounting control and accountability for the performance of government agencies, and (6) organizational commitment can moderate the relationship between the reporting system and the performance accountability of government agencies.Keywords: Utilization Of Information Technology; Accounting Control; Reporting Systems; Organizational Commitment; Performance Accountability Of Government Agencies.